The Effect Of Cigarette Smoking Habits On The Outcome Of Dental Implant Treatment (Journal of Namibian Studies : History Politics Culture, 2023)
he objective of this research was to investigate the impact of smoking behaviors and other potentially relevant factors on the success of dental implants. The study encompassed patients who underwent dental implant procedures .The study involved analyzing the relationship between characteristics of the implants and patients' smoking habits, as reported in questionnaires completed during routine medical check-ups. In addition to conventional statistical analyses, multiple linear regression models were used to assess the relative influence of various factors on the rate of implant survival.The overall long-term outcomes of the implant treatments were positive, with 7,680 implants studied. Of these, 7,359 (95.8%) were successful, while 321 (4.2%) were not. Regarding smoking behaviors, the study found that in univariate analysis, factors such as patients' smoking status (smoker/non-smoker), the quantity of smoking, exposure to passive smoking, and the duration since ex-smokers had quit smoking until the time of implantation were associated with implant survival. In the multivariable analysis, smoking status (smoker/non-smoker) and the amount of smoking, measured in pack years, were identified as factors influencing implant survival.